Membrane-active bacteriocins to control Salmonella in foods Are they the definite hurdle? - Chalon, Miriam Carolina (2012)
According to recent surveys salmonellosis is the main disease caused by foodborne microorganisms in many countries. Although traditional methods to control bacterial contamination in food are effective in controlling Salmonella, a major problem arises with fresh and organic food demanded by the market with little preparation and no chemical additives. Besides the development of new technologies that combine soft physical and chemical treatments in a way that causes minimal changes in food properties, antimicrobial peptides derived from natural sources are presented as an interesting alternative to chemical preservatives. There are many bacteriocins active against Salmonella and they could be used in the food industry alone or in combination with other hurdles to increase the anti-Salmonella effect in the so-called hurdle technology. However, further studies are necessary to demonstrate the safety of new bacteriocins and to improve their activity in different environmental conditions encountered during food processing. Moreover, nisin and pediocin PA-1 already approved as food preservatives by various government agencies, can be used along with other hurdles to control the pathogen in foods. In this paper the use of bacteriocins as hurdles for controlling Salmonella in the future is discussed and analyzed.